WOMEN IN THE BURNING FIRE OF PARTITION OF INDIA - Lubna Akram; Muhamed Ali Haniffa; Mohan Rathakrishnan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article is about the women of sub-continent who suffer during the partition riots. Women were brutally tortured, raped, kidnapped, killed and abducted. Being the honor and dignity of the community, they were targeted to degrade the men of other community. It was the brutal time that history ever seen in the name of the religion. Without committed any fault, any sin, these innocent girls and women were victimized in a very inhuman way. To safe their dignity and honor, they commit suicide, jumped into the well or take poison. Statistics were failed to show the pain, sufferings and psychological state of mind of all those women. Narratives and literature can be helpful to understand the feelings of the victim women.